Interlayer epitaxy of wafer-scale high-quality uniform AB-stacked bilayer graphene films on liquid Pt3Si/solid Pt - Ma, Wei; Chen, Mao-Lin; Yin, Lichang; Liu, Zhibo; Li, Hui; Xu, Chuan; Xin, Xing; Sun, Dong-Ming; Cheng, Hui-Ming; Ren, Wencai (Nature communications, 2019)
Large-area high-quality AB-stacked bilayer graphene films are highly desired for the applications in electronics, photonics and spintronics. However, the existing growth methods can only produce discontinuous bilayer graphene with variable stacking orders because of the non-uniform surface and strong potential field of the solid substrates used. Here we report the growth of wafer-scale continuous uniform AB-stacked bilayer graphene films on a liquid Pt 3 Si/solid Pt substrate by chemical vapor deposition. The films show quality, mechanical and electrical properties comparable to the mechanically exfoliated samples. Growth mechanism studies show that the second layer is grown underneath the first layer by precipitation of carbon atoms from the solid Pt, and the small energy requirements for the movements of graphene nucleus on the liquid Pt 3 Si enables the interlayer epitaxy to form energy-favorable AB stacking. This interlayer epitaxy also allows the growth of ABA-stacked trilayer graphene and is applicable to other liquid/solid substrates. Specific stacking sequence of graphene can enable observation of unusual properties however it has been difficult to obtain this over wider areas. Here, the authors report wafer-scale growth of 100% AB-stacked bilayer graphene films by CVD on liquid Pt 3 Si/solid Pt substrates showing high quality and improved mechanical properties comparable to the mechanically exfoliated flakes.